Psychological Symptoms and Behavioral Changes in Children and Adolescents During the Early Phase of COVID-19 Quarantine in Three European Countries - Francisco, Rita; Pedro, Marta; Delvecchio, Elisa; Espada, Jose Pedro; Morales, Alexandra; Mazzeschi, Claudia; Orgilés, Mireia (Frontiers in Psychiatry, 2020)
The coronavirus disease (COVID-19) pandemic forced the home confinement of the majority of population around the world, including a significant number of children and adolescents, for several weeks in 2020. Negative psychological effects have been identified in adults, but research about the impact of this type of social distancing measure on children and adolescents is scarce. The present study aimed to describe and compare the immediate psychological and behavioral symptoms associated with COVID-19 quarantine in children and adolescents from three southern European countries with different levels of restrictions (Italy, Spain, and Portugal). Parents of 1,480 children and adolescents (52.8% boys) between 3 and 18 years old (M = 9.15, SD = 4.27) participated in the study. An online survey using snowball sampling techniques was conducted during 15 days between March and April 2020, representing the early phase of the quarantine associated with COVID-19 outbreak. Parents answered questionnaires about sociodemographic data, housing conditions, immediate psychological responses during quarantine (e.g., anxiety, mood, sleep, and behavioral alterations), patterns of use of screens, daily physical activity, and sleep hours before and during the quarantine. The results revealed an increase in children's psychological and behavioral symptoms, increased screen-time, reduced physical activity, and more sleep hours/night. Italian children presented less psychological and behavioral symptoms compared with Portuguese and Spanish children. In general, hierarchical multiple regressions revealed that having an outdoor exit in the house (e.g., garden, terrace) contributed to lower levels of psychological and behavioral symptomatology. Future studies are needed to identify family and individual variables that can better predict children and adolescents' well-being during and after quarantine. Recommendations for families and implications for practice are discussed.